Analysis of ship structural integrity under various loading ‎conditions - Raj, Yeshwanth; Palanivelu, Rajendran (International Journal of Basic and Applied Sciences, 2025)
One of the main ways that ship structures fail is through fatigue damage. Usually, this type of damage starts at the structure’s weak points, ‎such as welded joints, cracks, and concentrated stress points. The primary focus of this study is fatigue damage that ships experience over ‎their operating lifespan as a result of cyclic stress, especially from waves. Though some are merely approximations, there are numerous ‎ways to different sea state situations. The most popular methods will be reviewed, including their strengths and weaknesses. Some of the ‎major theoretical methods discussed are energy spectrum methods in frequency and time domains, which estimate fatigue life based on ‎wave-related energy, amplitude, and wave loads. In addition, the evaluation of cyclic stress in specific hull girder and welded joint features ‎through finite element analysis will be presented to quantify the maximum stress range for future fatigue testing.